2010
DOI: 10.1148/radiol.09090608
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Bone Perfusion in Osteoporosis: Likely Causes in an Ovariectomy Rat Model

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.09090608/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 33 publications
(48 reference statements)
7
64
0
4
Order By: Relevance
“…Histologic (14) and radiologic (16-18) studies of osteoporotic bone have shown decreased interosseous blood flow. Ovariectomized rats develop reduced bone marrow blood flow together with reduced bone mineral density and evidence of endothelial dysfunction (19). In people with type 1 diabetes with microvascular complications, serum osteocalcin levels (a protein involved in bone mineralization) are lower than in those people without albuminuria (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Histologic (14) and radiologic (16-18) studies of osteoporotic bone have shown decreased interosseous blood flow. Ovariectomized rats develop reduced bone marrow blood flow together with reduced bone mineral density and evidence of endothelial dysfunction (19). In people with type 1 diabetes with microvascular complications, serum osteocalcin levels (a protein involved in bone mineralization) are lower than in those people without albuminuria (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, bone blood flow is significantly decreased while bone turnover is almost totally suppressed. In contrast, the significant increase in bone turnover in ovariectomized rodents has been associated with significant decreases in bone blood flow in a variety of studies using multiple techniques (111)(112)(113)(114). However, this vascular effect has been shown to strongly depend on genetic background (56), potentially explaining controversial reports of increased bone blood flow following rodent ovariectomy by quantifying microspheres (115)(116).…”
Section: Blood Flow For Maintenance Of Bonementioning
confidence: 99%
“…Previous investigations have discovered that osteoporosis may lead to decrease in BMSCs' organelles, reduction of BMSCs' viability, differentiation of BMSCs into adipocytes and decreased proliferation of BMSCs in vitro [5,18]. In senile osteoporosis, the molecule that maintains telomerase stability gradually diminishes, causing the telomerase to shorten, thus shortening the BMSCs and osteoblasts' life cycle which results in osteoporosis [19].…”
Section: Discussionmentioning
confidence: 99%